Sustaining organizational culture change in health systems - Willis, C; Saul, J; Bevan, H; Scheirer, M; Best, A; Greenhalgh, P; Mannion, R; Cornelissen, E; Howland, D; Jenkins, E; Bitz, J (Emerald, 2016)
Purpose – The questions addressed by this review are: first, what are the guiding principles underlying efforts to stimulate sustained cultural change; second, what are the mechanisms by which these principles operate; and, finally, what are the contextual factors that influence the likelihood of these principles being effective? The paper aims to discuss these issues. Design/methodology/approach – The authors conducted a literature review informed by rapid realist review methodology that examined how interventions interact with contexts and mechanisms to influence the sustainability of cultural change. Reference and expert panelists assisted in refining the research questions, systematically searching published and grey literature, and helping to identify interactions between interventions, mechanisms and contexts. Findings – Six guiding principles were identified: align vision and action; make incremental changes within a comprehensive transformation strategy; foster distributed leadership; promote staff engagement; create collaborative relationships; and continuously assess and learn from change. These principles interact with contextual elements such as local power distributions, pre-existing values and beliefs and readiness to engage. Mechanisms influencing how these principles sustain cultural change include activation of a shared sense of urgency and fostering flexible levels of engagement. Practical implications – The principles identified in this review, along with the contexts and mechanisms that influence their effectiveness, are useful domains for policy and practice leaders to explore when grappling with cultural change. These principles are sufficiently broad to allow local flexibilities in adoption and application. Originality/value – This is the first study to adopt a realist approach for understanding how changes in organizational culture may be sustained. Through doing so, this review highlights the broad principles by which organizational action may be organized within enabling contextual settings.